Symbol – ikona tajemnicy - Bardski, Krzysztof (Verbum Vitae, 2009)
Throughout the centuries, the more-than-literal interpretation of the Bible was present in the tradition of the Church. Symbols made out of biblical literary motifs expressed deep theological and human concepts. They made visible what otherwise was invisible. Our article presents three symbols rooted in the biblical text that acquired new spiritual meanings in the ancient and medieval interpretation of the Scripture: wings, tree and bow.